PROFITABILITAS, LIKUIDITAS DAN NILAI PERUSAHAAN (INDUSTRI PROPERTI DAN REAL ESTATE YANG LISTED DI PT. BEI PADA TAHUN 2011-2014) - Setiawanta, Yulita (Jurnal Penelitian Ekonomi dan Bisnis, 2016)
This research aims to examine as partially the effect of ROA, ROEand CR on Firm Value of real estate and property company in Indonesia stock Exchange . Independent variables used are ROA (Return On Assets), ROE (Return On Equity) and CR (Current Ratio). The total sample on this research obtained to 174 data oberseved. The data analyzed is secondary data obtained from Indonesia stock Exchange. The analytical method in this research uses descriptive statistic, classical assumption test, F test, hypothesis test, and coefficient of determination test. The result of this study shows that ROA and CR have no significant effect on firm value, meanwhile ROE has the effect on frim value,Keyword: : Firm Value ; Return On Asset; Return On Equity; Current ratio.